Chromosomes of Helleborus grown in Turkey. - Sezer, Nursel (Marmara Pharmaceutical Journal, 1988)
Chromosome numbers have been counted for 2 species of Helleborus (Ranunculaceae) from Turkey: H.vesicarius Aucher and H.orientalis Lam.